Avaliação do pré-natal em gestantes com sífilis e a prevenção da sífilis congenita na rede pública de um munícipio do sul do Brasil - Paim, Caroline Citoula (2019)
The purpose of this study is to analize the quality of the prenatal care in the combat of congenital syphilis, proper diagnosis and treatment, according to what is recommended by the Health Ministry, in the PHC, in the city of Santa Maria, Rio Grande do Sul, Brazil. Thus, the research was justified by the need to know and understand the gaps in prenatal care provided to pregnant women with syphilis, as well as the offer of tests for the classification of the disease and offering suitable treatment. It was a descriptive study of quantitative approach, through a semi structured questionnaire with closed questions. The results were tabulated and analyzed. The data were processed and analyzed from the construction of a database (Excel® 2007) and a specific program of analysis for the accomplishment of the objectives of the research - the software Statistical Package for Social Science 15.0 (SPSS). The adopted method, according to the goals, was the descriptive and explanatory research. The results were divided into topics, from the questionnaire, addressing the context of care provided to pregnant women with syphilis in PHC in the city of Santa Maria. They will be exposed in this sequence: I – Description of the professional participating in the study; II - Description of the prenatal care at the Health Unit; and III – Prevention of vertical transmission of syphilis. The population of this study was composed of 50 participants, all PHC workers, doctors and nurses who perform prenatal care, 27 are ESF professionals and and 23 UBS professionals. It was observed, through the questionnaire responses, that although most of the pregnant women start prenatal care before the 12th week of pregnancy and that they attend seven or more visits, professionals report that the difficulty for the efficacy of the therapy lies in the non adherence of the pregnant women to prenatal or late prenatal initiation (after 28 weeks). It can be verified that these data are not congruent, and it is not possible to blame the pregnant women, since the participants report that the majority of pregnant women adheres to prenatal care before the 12th gestational week, this could not be the cause for the outcome of congenital syphilis. Although an approach is taken to the partners of the pregnant women, the professionals point out the difficulty of their adherence by the non-attendance in the appointments, a fact that shows that probably the way the man's prenatal care is being conducted is inadequate. It was possible to conclude that even with the agreement of the governmental spheres to eradicate congenital syphilis, it was observed the persistence of the pathology and the permanence of inadequate behaviors in the management of the disease by the professionals who attend prenatal care of pregnant women with syphilis.